The Cultural-Religious Diversity and Civic Upbringing at the Catholic School - Aldona Zakrzewska (Nicolaus Copernicus University in Toruń, 2017)
The basis for the discussion is civic upbringing which is introduced in Catholic schools in the spirit of openness of the children and teenagers to the cultural-religious diversity which is more and more visible in the Polish social reality. It is especially difficult from the social perspective. On the one hand each group wants to live in tolerance, on the other hand it wants to keep its identity. Besides it is not easy in the perspective of the mission of the Catholic school. It results from the fact that although it declares building unity in diversity, the educational and upbringing process of the school determines the specific point of view.